Evaluation of eco‐friendly zwitterionic detergents for enveloped virus inactivation. Issue 4 (9th November 2016) - Conley, Lynn; Tao, Yinying; Henry, Alexis; Koepf, Edward; Cecchini, Douglas; Pieracci, John; Ghose, Sanchayita
ABSTRACT: Inclusion of a detergent in protein biotherapeutic purification processes is a simple and very robust method for inactivating enveloped viruses. The detergent Triton X‐100 has been used for many years and is part of the production process of several commercial therapeutic proteins. However, recent ecological studies have suggested that Triton X‐100 and its break‐down products can potentially behave as endocrine disrupters in aquatic organisms, raising concerns from an environmental impact perspective. As such, discharge of Triton X‐100 into the waste water treatment plants is regulated in some jurisdictions, and alternative detergents for viral inactivation are required. In this work, we report on the identification and evaluation of more eco‐friendly detergents as viable replacements for Triton X‐100. Five detergent candidates with low to moderate environmental impact were initially identified and evaluated with respect to protein stability, followed by proof‐of‐concept virus inactivation studies using a model enveloped virus. From the set of candidates lauryldimethylamine N‐oxide (LDAO) was identified as the most promising detergent due to its low ecotoxicity, robust anti‐viral activity (LRV >4 at validation set‐point conditions with X‐MuLX), and absence of any negative impact on protein function. This detergent exhibited effective and robust virus inactivation in a broad range of protein concentrations, solution conductivities, pHs, and in several different cell culture fluid matrices. The only process parameter which correlated with reduced virus inactivation potency was LDAO concentration, and then only when the concentration was reduced to below the detergent's critical micelle concentration (CMC). Additionally, this work also demonstrated that LDAO was cleared to below detectable levels after Protein A affinity chromatography, making it suitable for use in a platform process that utilizes this chromatographic mode for protein capture. All these findings suggest that LDAO may be a practical alternative to Triton X‐100 for use in protein therapeutic production processes for inactivating enveloped viruses. Biotechnol. Bioeng. 2017;114: 813–820. © 2016 Wiley Periodicals, Inc. Abstract : To ensure the safety of cell culture derived biotherapeutics, manufacturing processes of such molecules need to incorporate steps capable of inactivating or removing viruses. In this study we identified and tested several eco‐friendly, zwitterionic, detergents for their ability to inactivate enveloped viruses, and discovered that lauryldimethylamine N‐oxide provided very potent inactivation. Studies investigating the robustness of this step revealed that only very low detergent concentrations negatively impacted inactivation.